PESAN ANTIPERUNDUNGAN DALAM IKLAN KOMERSIAL: Kasus iklan Burger King versi “Bullying Jr.” - Maulianza, Medo; Galib, Septrani (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2018)
This study describes the identification of anti-bullying message and the construction of social reality in Burger King ad version “Bullying Jr.” through semiotics analysis on signs. Semiotics theory used in this study is focusing on Roland Barthes perspective. The analysis shows that majority of society tends to be antipathy towards bullying that happens around them. The message included in this advertisement is for the society to be braver to fight bullying around them. To cite this article (7th APA style): Maulianza, M. & Galib, S. (2018). Pesan Antiperundungan dalam Iklan Komersial: Kasus Iklan Burger King versi “Bullying Jr.”[Anti-Bullying Message in Commercial Ads]. Journal Communication Spectrum, 8(2), 113-132. http://dx.doi.org/10.36782/jcs.v8i2.1850